2017
DOI: 10.1111/papt.12090
|View full text |Cite
|
Sign up to set email alerts
|

Seeking help for obsessive compulsive disorder (OCD): a qualitative study of the enablers and barriers conducted by a researcher with personal experience of OCD

Abstract: People with OCD may face a wide range of barriers to seeking help, including concern about the reaction of health professionals. The level of awareness, kindness, and understanding shown by first-line practitioners can be very important to those seeking help. Acknowledging a person's journey prior to seeking help is likely to foster trust between therapist and patient. Some barriers to seeking help, for example, fear of criminalisation, may continue to have an important effect afterwards unless sensitively exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Increased social support and having more than five close friends or relatives were associated with decreased risk of experiencing stigma in the univariate analysis. This is consistent with a number of other studies including Rusch et al [ 21 ], Robinson et al [ 37 ] and Moore & Ayers [22]- who found that use of internet forums by women with post-natal mental illness enabled them to disclose their illness to others. This raises an interesting question for future work in terms of the distinction between social support from peers with a diagnosis of mental illness themselves, and those without mental illness.…”
Section: Discussionsupporting
confidence: 91%
“…Increased social support and having more than five close friends or relatives were associated with decreased risk of experiencing stigma in the univariate analysis. This is consistent with a number of other studies including Rusch et al [ 21 ], Robinson et al [ 37 ] and Moore & Ayers [22]- who found that use of internet forums by women with post-natal mental illness enabled them to disclose their illness to others. This raises an interesting question for future work in terms of the distinction between social support from peers with a diagnosis of mental illness themselves, and those without mental illness.…”
Section: Discussionsupporting
confidence: 91%
“…These findings, together with other reasons for delayed help-seeking identified in the literature (e.g. stigma[22]), offer insight into the reasons for the substantial delay in help-seeking observed in OCD [23]. The findings suggest that the conceptualisation of OCD as a health problem is a crucial step necessary in initiating appropriate health related behaviour, such as seeking treatment through the medical system including psychiatry or clinical psychology.…”
Section: Discussionmentioning
confidence: 71%
“…sexual or religious obsessions) or other “internal/cognitive” factors (e.g. reluctance to admit that there may be a problem), fear of criminalization and/or other stigma related factors, or just not knowing where to find help [4, 23]. Educational campaigns presenting OCD as an illness that can be cured and resources to improve access to mental health services could in the near future shorten the delay in seeking treatments.…”
Section: Discussionmentioning
confidence: 99%